2022
DOI: 10.3390/jof8111200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Species and Records of Dictyosporiaceae from Freshwater Habitats in China and Thailand

Abstract: China and Thailand are rich in fungal diversity with abundant freshwater resources that are favorable for numerous fungal encounters. Resulting from this, the majority of the Dictyosporiaceae species reported were from these two countries. During the investigation on the diversity of lignicolous freshwater fungi in the Greater Mekong Subregion, eleven collections of cheirosporous species on submerged wood were collected from lentic and lotic habitats in China and Thailand. Phylogenetic analysis that combined n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Within Dictyosporaceae, Dictyocheirospora and Dictyosporium are the two most prominent genera that accommodate the majority of freshwater species, with 11 and 9 reported freshwater species, respectively [24,25]. A geographical distribution review showed that numerous species within the family were reported from China and Thailand [2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Within Dictyosporaceae, Dictyocheirospora and Dictyosporium are the two most prominent genera that accommodate the majority of freshwater species, with 11 and 9 reported freshwater species, respectively [24,25]. A geographical distribution review showed that numerous species within the family were reported from China and Thailand [2].…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic relationships between genera in Dictyosporiaceae have been well investigated using DNA sequence data [1,2,7,12,24,25]. However, the interspecific phylogenetic relationships in some cases remain ambiguous due to the limitation of insufficient sequence data included in the phylogenetic tree.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations